Compensation Between Cloud Feedback and Aerosol‐Cloud Interaction in CMIP6 Models. Issue 4 (23rd February 2021) - Wang, Chenggong; Soden, Brian J.; Yang, Wenchang; Vecchi, Gabriel A.
Abstract: The most recent generation of climate models (the 6th Phase of the Coupled Model Intercomparison Project) yields estimates of effective climate sensitivity (ECS) that are much higher than past generations due to a stronger amplification from cloud feedback. If plausible, these models require substantially larger greenhouse gas reductions to meet global warming targets. We show that models with a more positive cloud feedback also have a stronger cooling effect from aerosol‐cloud interactions. These two effects offset each other during the historical period when both aerosols and greenhouse gases increase, allowing either more positive or neutral cloud feedback models to reproduce the observed global‐mean temperature change. Since anthropogenic aerosols primarily concentrate in the Northern Hemisphere, strong aerosol‐cloud interaction models produce an interhemispheric asymmetric warming. We show that the observed warming asymmetry during the mid to late 20th century is more consistent with low ECS (weak aerosol indirect effect) models. Plain Language Summary: The response of clouds to surface temperature change can amplify or dampen the greenhouse gas induced warming, also known as cloud feedback. We find that in the latest generation of climate models, those models with a more positive cloud feedback tend to have a stronger cooling effect from aerosol‐cloud interaction. The compensation between cloud feedback and aerosol‐cloud interaction enables models to reproduce the historical global‐mean temperature change. In spite of having significantly different surface temperature sensitivity to increasing CO2, the historical record of global‐mean temperature is not a strong constraint in distinguishing these models. However, the interhemispheric difference in temperature over the 20th century provides a constraint that distinguishes the models that have a large or small sensitivity to increasing CO2 . Over the 20th century, changes in anthropogenic aerosols were mostly concentrated in the Northern Hemisphere. Consequently, models with strong or weak aerosol‐cloud interactions produce different warming asymmetry over the historical period, and the observed warming asymmetry is more consistent with the models that have weak aerosol‐cloud interactions (and less positive cloud feedback). This study can help us better understand and reduce the uncertainty in the projected future warming. Key Points: Models with more positive cloud feedback tend to have more negative aerosol‐cloud interaction This compensation relationship enables the models to match the historical warming even with a large spread in climate sensitivity Historical interhemispheric warming indicates the high climate sensitivity models overestimate the aerosol‐cloud interaction